ANALISIS PENGARUH KEBIJAKAN PERDAGANGAN DUNIA TERHADAP TREN EKSPOR INDONESIA DALAM ERA GLOBALISASI - Farhan Kaustari Fadia; Nursani Alvia Siregar, Nur Fadillah Hayati, Putri Amirah Hajarani, Sabilla Cahya Kinanti; Dwita Sakuntala (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to analyze the influence of world trade policies on Indonesia's export trends. In the era of globalization, the dynamics of international trade are greatly influenced by policies such as tariffs, quotas, and trade agreements implemented by various countries. This study uses secondary data from the Central Bureau of Statistics (BPS) and international trade reports in the last five years to understand how changes in global policies, such as trade wars, protectionism, and free trade agreements (FTAs), have impacted the volume and composition of Indonesia's exports. The results of the analysis show that world trade policies significantly affect Indonesia's exports, especially for leading commodities such as palm oil, coal, and textile products. In addition, the implementation of free trade policies provides opportunities to increase market access, although there are challenges in the competitiveness of local products. This study provides insight for policy makers to formulate adaptive and competitive trade strategies in facing global dynamics